Inhomogeneous cancellation conditions and Calderón–Zygmund type operators on hp. (December 2022) - Dafni, Galia; Lau, Chun Ho; Picon, Tiago; Vasconcelos, Claudio
Abstract: In this work we present a new approach to molecules on Goldberg's local Hardy spaces h p ( R n ), 0 < p ≤ 1, assuming an appropriate cancellation condition. As applications, we prove a version of Hardy's inequality and improved continuity results for inhomogeneous Calderón–Zygmund operators on these spaces.